PERAN MARKETING COMMUNICATION DALAM MENDUKUNGSUSTAINABLECOMPANY (STUD I KASUS MARCOMM TOYOTA- NASMOCO GOMBEL) - IGN. Wisnu Ananta Praja (Institut Seni Indonesia Yogyakarta, 2013)
MarComm is a synergy, creativity, integration and integrated marketing communications byutilizing a variety of different communication elements in order to create coherence in each field to makeit more cohesive and coherent. Marcomm responsibility is to ensure proper communication is achieved;established corporate image, brand awareness is awakened, etc .. , If this can be achieved then Marcommcan be said to have goals and staying maintain the continuity of the activities I sustainable business withinthe company.Keywords: MarComm, Coherence, Sustainable Company,